Project management bootcamp a step-by-step guide - Cross, Peter (Routledge, 2024)
Project Management Bootcamp is a pragmatic guide for those who need to understand how to deliver projects successfully. The reader journeys through a project stage by stage, discovering what project managers commonly need to achieve at each step. Each step is supported by tables, charts, tips, and tools, which readers may adopt or adapt to their needs, and different ways of organising and delivering projects, including agile approaches, are considered.Because theory can only get you so far, a key element of the book is learning from real projects drawing on the experience of project managers working across three continents. Each chapter ends with challenges to readers to reflect on their learning, which can be based on a theoretical case study or their own project. The result is a reflective framework that charts their learning and their project management journey from initiation to closure.Project Management Bootcamp is essential reading for junior and mid-level career project managers, as well as any professionals who finds themselves in charge of a project and are unsure how to get the best result. Students in business and management courses at undergraduate and postgraduate levels will also value its setting of theory into a practical context
Introduction; Chapter 1 Grasping the Basics ; Chapter 2 Framing our Project; Chapter 3 Preparing for Launch Part 1: Compiling the Four Document Set; Chapter 4 Preparing for Launch Part 2: Writing the Business Case; Chapter 5 Preparing for Launch Part 3: The Project Plan; Chapter 6 Project Team Creation & Management: Round up the Usual Suspects; Chapter 7 Communications and Engagement: Who is Holding the Stake?; Chapter 8 Managing Risks and Issues: What could possibly go wrong? ; Chapter 9 Managing Change: Getting to Grips with the Real World; Chapter 10 Supplier Management: Your supplier is your supplier – not your friend; Chapter 11 Monitoring, Controlling, and Reporting: Keeping on Top of Progress; Chapter 12 Managing and Realising the Benefits: Just when you thought it was all over. (1); Chapter 13 Project Closure: Just when you thought it was all over. (2); Chapter 14 Project First Aid: How to stop a project bleeding to death; Appendix 1 Facilitating Discovery; Appendix 2 Partnership Working in UK Construction – A Journey from Conflict to Collaboration
Keywords: bicssc / Building construction & materials; bicssc / Economics; bicssc / Production & quality control management; bicssc / Project management; bicssc / Environmental science, engineering & technology; bicssc / Engineering - general; bisacsh / TECHNOLOGY & ENGINEERING / Project Management; bisacsh / BUSINESS & ECONOMICS / General; bisacsh / BUSINESS & ECONOMICS / Management Science